2019
DOI: 10.1007/s10021-019-00461-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-rainfall Moisture: A Key Driver of Microbial Respiration from Standing Litter in Arid, Semiarid, and Mesic Grasslands

Abstract: Models assume that rainfall is the major moisture source driving decomposition. Non-rainfall moisture (NRM: high humidity, dew, and fog) can also induce standing litter decomposition, but there have been few measurements of NRM-mediated decomposition across sites and no efforts to extrapolate the contribution of NRM to larger scales to assess whether this mechanism can improve model predictions. Here, we show that NRM is an important, year-round source of moisture in grassland sites with contrasting moisture r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 62 publications
0
72
0
Order By: Relevance
“…Dry periods lasting for more than 100 hours were not uncommon at the Rain Site ( Supplementary Figure 1 ). Previous work has shown that wet events are longer at the NRM Site ( Evans et al, 2020 ); for example, at the NRM Site, only 5% of wet events lasted two hours or less while at the Rain Site 22% of wet events were this short. Mean temperature during wet events was only slightly lower at the NRM Site, which had a narrower temperature range (range 1.6–26.9°C) than did the Rain Site (range −0.7–39.1°C).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Dry periods lasting for more than 100 hours were not uncommon at the Rain Site ( Supplementary Figure 1 ). Previous work has shown that wet events are longer at the NRM Site ( Evans et al, 2020 ); for example, at the NRM Site, only 5% of wet events lasted two hours or less while at the Rain Site 22% of wet events were this short. Mean temperature during wet events was only slightly lower at the NRM Site, which had a narrower temperature range (range 1.6–26.9°C) than did the Rain Site (range −0.7–39.1°C).…”
Section: Resultsmentioning
confidence: 87%
“…In many arid and semi-arid systems, organisms cope with water limitation by using non-rainfall moisture (fog, dew, and atmospheric water vapor; hereafter “NRM”) as a supplemental water source ( Dirks et al, 2010 ; Jacobson et al, 2015 ; Gliksman et al, 2017 ; Wang et al, 2017 ). In some grasslands, dew can occur as frequently as 95% of nights ( Ritter et al, 2019 ) and recent work has demonstrated that NRM is an important driver of decomposition in both arid and mesic grasslands alike ( Evans et al, 2020 ). NRM can be a particularly important moisture source for standing litter (senesced litter that has not fallen to the ground surface yet), where frequent wetting and subsequent microbial growth can “prime” litter for decomposition once it reaches the soil surface ( Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also measured respiration without any addition of water and found no significant difference in respiration rates between untreated soils and soils undergoing vapor equilibration (Figure 3a). However, recent studies have highlighted that in some ecosystems (e.g., arid ecosystems), non‐rainfall moisture (high humidity, dew, and fog) can significantly increase microbial activity (Evans, Todd‐Brown, Jacobson, & Jacobson, 2019). The increase in respiration rates following water addition to dry soils is a common phenomenon (Birch, 1958).…”
Section: Resultsmentioning
confidence: 99%
“…undergoing vapor equilibration (Figure 3a). However, recent studies have highlighted that in some ecosystems (e.g., arid ecosystems), nonrainfall moisture (high humidity, dew, and fog) can significantly increase microbial activity (Evans, Todd-Brown, Jacobson, & Jacobson, 2019).…”
Section: F I G U R Ementioning
confidence: 99%